Biotechnological uses of RNAi in plants: risk assessment considerations. Issue 3 (March 2015) - Casacuberta, Josep M.; Devos, Yann; du Jardin, Patrick; Ramon, Matthew; Vaucheret, Hervé; Nogué, Fabien
<x xml:space="preserve">Abstract</x> RNAi offers opportunities to generate new traits in genetically modified (GM) plants. Instead of expressing novel proteins, RNAi-based GM plants reduce target gene expression. Silencing of off-target genes may trigger unintended effects, and identifying these genes would facilitate risk assessment. However, using bioinformatics alone is not reliable, due to the lack of genomic data and insufficient knowledge of mechanisms governing mRNA–small (s)RNA interactions.